Chemical and photo-chemical bonding of polymer and silica fibers - Chychłowski, Miłosz; Ertman, Sławomir; Woliński, Tomasz R. (Photonics Letters of Poland, 2014)
In this paper we present a permanent way of connecting two different fiber types. The one of them is a novel fiber based on polymer as a main construction material, with a build-in photonic structure in its cladding. Second type is a typical silica single-mode fiber. Due to differences of base materials thermal bonding is impossible in order to keep both structures intact. However, chemical bonding by using appropriate materials can connect two types of fibers without disturbing their inner structures. Additional advantage of the proposed chemical “splicing” method is that adhesive can act as index matching material decreasing losses. Full Text: PDF References P.St.J. Russell, J.C. Knight, T.A. Birks, B.J. Mangan, W.J. Wadsworth, "Photonic Crystal Fibers", Science 299, 358-362 (2003) CrossRef J.C. Knight, "review article Photonic crystal fibres", Nature 424, 847-851 (2003) CrossRef S. Ertman, A. H. Rodríguez, M.M. Tefelska, M.S. Chychłowski, D. Pysz,R. Buczyński, E. Nowinowski-Kruszelnicki, R Dąbrowski, T.R. Woliński, Index guiding photonic liquid crystal fibers for practical applications", Journal of Lightwave Technology 30 (2012), pp. 1208 CrossRef P. Mergo, M. Gil, K. Skorupski, J. Klimek, G. Wójcik, J. Pędzisz, J. Kopec, K. Poruraj, L. Czyzewska, A. Walewski, A. Gorgol, "Low loss poly(methyl methacrylate) useful in polymer optical fibres technology", Phot. Lett. Poland. 5, 170 (2013) CrossRef S. Ertman et al. submitted to Photonics Lett. PL. CrossRef J. M. Cariou, J. Dugas, L. Martin, and P. Michel, "Refractive-index variations with temperature of PMMA and polycarbonate" ,Applied Optics, Vol. 25, Issue 3, pp. 334-336 (1986) CrossRef T. Kurokawa, N. Takato, Y. Katayama, "Polymer optical circuits for multimode optical fiber systems", Applied Optics, Vol. 19, Issue 18, pp. 3124-3129 (1980) CrossRef R. Kitamura, L. Pilon, M. Jonasz, "Optical constants of silica glass from extreme ultraviolet to far infrared at near room temperature", Applied Optics, Vol. 46, Issue 33, pp. 8118-8133 (2007) CrossRef